Approach to Five Year Plan - Planning Commission (Planning Commission)
Every Sanskrit Epic used to begin with an invocation to favourite duty. Every note the development of our State has to begin with lination and analysis of our comparative poverty. While it has to be felt than dissected, the standard economic indicators will provide the extent a degree of regional imbalance and the comparative status of Orissa.
Approach to Five Year Plan